ICHTYOFAUNA COMMUNITY STRUCTURE OF THE FINIMA NATURE PARK LAKE, BONNY ISLAND, RIVERS STATE, NIGERIA. - Ibim, A.T; Amadi, A.; Eziefule, G.S. (Nigerian Journal of Fisheries, 2019)
A study to determine the Community structure of the fish fauna was carried out. The aim of the study was to identify and document the Ichtyofauna community. A four-month survey was carried out. Fish samples were caught using traps of various types and sizes, and cast nets of 2mm mesh size. The diversity, composition, and abundance of the fishes from the Lake was assessed using standard methods. The results revealed a composition of 7 species (Hemichromis fasciatus, Coptodon guineensis, Coptodon zilli, Sarotherodon melanotheron, Sarotherodon galilaeus, Parachana obscura and Hydrocynus brevis) from 3 families (Cichlidae, Alestidae and Channidae). The Shannon Weiner diversity index revealed the family Cichlidae as the most diverse (84%) with 5 species, followed by Alestidae (13%) with 1 species, and Channidae (2%) with 1 species. The relative abundance revealed the Cichlidae as most abundant family, and the Hemichromis fasciatus species with 54.74% as most abundant species, while the Coptodon guineensis (2.1%) and P. obscura, (2.1%) were the least abundant. In conclusion, the fish community status is poor, as almost all the species therein are extremely low (rare), except for H. fasciatus which itself is “few”